Implementasi Nilai Karakter dalam Perencanaan Pembelajaran Sejarah - Refli Surya Barkara; Beni Idham; Dina Amelia; Ilham Arizka; Muhammad Fadly (UIN Imam Bonjol Padang, 2023)
This research oriented from many behaviors phenomenon which is caused by low of students’ nasionalism attitude such as students less using Indonesian language well and correctly, it is found that many students do not want to participate in flag ceremony well and correctly. At the last appears the questions does history learning has been implemented well, then why students’ nasionalism attitude still low. Therefore, the purposes of this research are to define how the efforts of students nationalism building through history learning. The type of this research is qualitative research with case study approach. Based on the result acquired finding that Effort of students nasionalism building through history learning in SMAN 2 Lubuk Basung and ekstracurricular activity